Pelatihan Deteksi Karier Thalassemia kepada Bidan di Banyumas - Lantip Rujito; Qodri Santosa; Diyah Woro Dwi Lestari; Eman Sutrisna; Ariadne Tri Hapsari (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Thalassemia ranks top on the list of diseases caused by the monogenic mechanism, especially in hematology disorders. Currentlly, Thalassemia ranks 5th in the national health insurance coverage. Prevention is the only effective way to control the clinical, psychological and financial burden of the country. One aspect of prevention is the discovery and genetic counseling process of persons who carry the mutan gene or carier of thalassemia. Midwives as the most peripheral health workers in the national health system are very important in their role in the discovery and counseling of these people. Provision of sufficient knowledge and skills of midwives can be a reliable tool in efforts to prevent thalassemia in the community.